(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Text mining is a variant of data mining that attempts in finding an interesting pattern from largerdatasets. The text databases have been growing rapidly owing to the increase in amount of informationthat is available in the form of electronic publications, from e-mail and World Wide Web. Technically, textmining is one of the automated methods that exploit the large knowledge available from text document.Natural Language Processing (NLP) has several applications in web search, retrieval of information,ranking and classification of documents where text classification is an important task. Text classificationintends to provide high quality textual representation accessed from the digital forms of documentavailable online and build high quality classifiers. Current research explores the Machine learningclassifiers for text classification.